Magnesium doped zinc oxide : Synthesis, characterization and catalytic photodegradation of methylene blue dye application / Nurul Syazwani Zainudin - Zainudin, Nurul Syazwani (Faculty Of Applied Sciences, 2017)
Pure ZnO and Mg-doped ZnO with different concentration (I mo1 %, 3 mo1 %, 5 Mo1 %, 7 mo1 % and 10 mo1 %) nanoparticles were synthesized with sol-gel method. The pure ZnO am Mg-doped ZnO at different concentration was characterized by using XRD, FESEM am UV - visible spectroscopy respectively. The structural characteristics were examined using XRD am SEM with EDS. XRD analysis reveals that all simple crystaIlizes in polycrystalline nature with wurtzite lattice am exhibit no other impurity phase. The average crystallite size decreases with increase in Mg concentration The protocatalytic activity of Mg-doped ZnO shows that the protodegradation gradually increases with increasing the concentration of Mg dopant showing to increase the UV absorbance of ZnO nanoparticles. From the protocatalytic activity the protodegradation constant, k is obtained am showed that the value k of pure ZnO is higher than Mg-doped ZnO